2017
DOI: 10.18293/seke2017-151
|View full text |Cite
|
Sign up to set email alerts
|

A Tailor made System for providing Personalized Services

Abstract: Abstract-Today, the existing technologies, such as smartphone and other pervasive devices, can be used for context awareness and help people to undertake conscious choices. In fact, unlike what happened in the past, all of these data are managed and contextualized for the particular application. We need to understand, select, treat and finally opportunely expose these data. In this scenario, there are many Context Aware applications. This paper introduces a tailor made system for providing personalized service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Wu et al (neural news recommendation with personalized attention (NPA)) [31] suggested personalized convolutional neural networks that adopt the embedding of user IDs as the queries of the correlations between words and news. The meta-context dimension tree (Meta CDT) was proposed for the selection of the most suitable contents and services for a user in a certain context, and was used in a practical context-aware application by Colace et al [32] and Casillo et al [33]. The approach has strength in tailoring the information domain according to the user's needs as well as in analyzing relevant features of context models.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (neural news recommendation with personalized attention (NPA)) [31] suggested personalized convolutional neural networks that adopt the embedding of user IDs as the queries of the correlations between words and news. The meta-context dimension tree (Meta CDT) was proposed for the selection of the most suitable contents and services for a user in a certain context, and was used in a practical context-aware application by Colace et al [32] and Casillo et al [33]. The approach has strength in tailoring the information domain according to the user's needs as well as in analyzing relevant features of context models.…”
Section: Introductionmentioning
confidence: 99%